2016
DOI: 10.1007/s13277-016-4869-5
|View full text |Cite
|
Sign up to set email alerts
|

Elevated STMN1 promotes tumor growth and invasion in endometrial carcinoma

Abstract: Overexpression of stathmin (STMN1) is closely linked to tumor metastases and poor prognosis in endometrial carcinoma (EC). However, the underlying mechanism is little known. In the present study, we investigated the expression of STMN1 in EC. Subsequently, we assessed the role of STMN1 in EC cell proliferation and migration. Our data show that STMN1 is upregulated in EC, and elevated expression of STMN1 is correlated positively with tumor stage and lymph node metastasis. In vitro, forced expression of STMN1 pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 21 publications
1
21
0
Order By: Relevance
“…In hepatoma HCCLM3 cells, studies found that STMN1 siRNA could obviously inhibit cell proliferation and migration (24). In human endometrial carcinoma (EC) cell line Ishikawa, STMN1 was further identified showing a positive effect on cell viability and migration (25). In agreement with previous reports, our studies in vitro suggested that reduced expression of STMN1 in FaDu cells obviously induced a cell cycle arrest in G1 phase, accompanied by inhibited cell viability.…”
Section: Discussionmentioning
confidence: 99%
“…In hepatoma HCCLM3 cells, studies found that STMN1 siRNA could obviously inhibit cell proliferation and migration (24). In human endometrial carcinoma (EC) cell line Ishikawa, STMN1 was further identified showing a positive effect on cell viability and migration (25). In agreement with previous reports, our studies in vitro suggested that reduced expression of STMN1 in FaDu cells obviously induced a cell cycle arrest in G1 phase, accompanied by inhibited cell viability.…”
Section: Discussionmentioning
confidence: 99%
“…There are two sites, observed in seven of the omics studies: STMN1 S‐25 and TPR S‐2155, which are direct ERK targets. STMN‐1 is responsible for microtubule filament organization, which plays a role in tumor growth and invasion , the S‐25 phosphorylation site on this oncoprotein is known to play a role in metastasis. TPR is a member of the nuclear pore complex that regulates the transport of mRNA and some proteins such as ERK and it also plays a role in mitosis .…”
Section: Analysis Of the Erk Target Sitesmentioning
confidence: 99%
“…Stathmin 1 (STMN1), a major microtubule-depolymerizing protein, serves as a prognostic marker for multiple cancers, including NSCLC,15 gallbladder carcinoma,16 and colon cancer 17. STMN1 has been found to destabilize microtubules and plays an important role in the regulation of cell cycle progression and tumor metastasis 18,19…”
Section: Introductionmentioning
confidence: 99%